PENERAPAN STRATEGI PEMBELAJARAN DIRECTED READING ACTIVITY UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV DI UPT SPF SD NEGERI UJUNG TANAH 1 KOTA MAKASSAR - Rosdiah Salam; Andi Makkasau; Ayuni, Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of the Directed Reading Activity (DRA) learning strategy in improving the reading comprehension skills of fourth-grade students at UPT SPF SD Negeri Ujung Tanah 1, Makassar City. This study was motivated by students' low ability in understanding reading texts, particularly in determining the main idea of a paragraph. The subjects of this study were the teacher and students of Grade IV B, while the objects were the DRA learning strategy and students' reading comprehension skills. This study was a Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. Data were collected through observation and tests, then analyzed using qualitative and quantitative techniques. The results showed that teacher teaching activities in Cycle I, Meeting 1 were in the sufficient category and Meeting 2 was in the less category. In Cycle II, teacher activities improved very significantly, with both Meeting 1 and Meeting 2 in the good category. Regarding student learning activities, in Cycle I both Meeting 1 and Meeting 2 were in the sufficient category, which then increased in Cycle II to the good category in both meetings. Furthermore, the results of the reading comprehension skills test in Cycle I were in the less category, then increased significantly in Cycle II to the good category. Thus, it can be concluded that the application of the Directed Reading Activity (DRA) learning strategy can improve the reading comprehension skills of fourth-grade students at UPT SPF SD Negeri Ujung Tanah 1, Makassar City.